2012
DOI: 10.1182/blood-2011-08-376426
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of monocytes/macrophages by tissue factor-mediated coagulation is essential for metastatic cell survival and premetastatic niche establishment in mice

Abstract: Tissue factor (TF) expression by tumor cells correlates with metastasis clinically and supports metastasis in experimental settings. However, the precise pathways coupling TF to malignancy remain incompletely defined. Here, we show that clot formation by TF indirectly enhances tumor cell survival after arrest in the lung, during experimental lung metastasis, by recruiting macrophages characterized by CD11b, CD68, F4/80, and CX 3 CR1 (but not CD11c) expression. Genetic or pharmacologic inhibition of coagulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
280
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(298 citation statements)
references
References 46 publications
(89 reference statements)
5
280
0
2
Order By: Relevance
“…[30][31][32] We observed that while N202.1A tumors in the lung induced a low level of CD681 macrophages secreting IL-10, B16 melanoma cells strongly promoted the presence of double-stained CD681IL-101 cells, suggesting the potential of the latter model to induce an immunosuppressive microenvironment. Accordingly, Gil-Bernabè et al 44 have recently observed in lungs from mice injected with B16 melanoma cells the selective recruitment of CD681 macrophages essential for tumor cell survival. These observations are consistent with studies showing that alveolar macrophages in the presence of some growing tumors become immunosuppressive, 33,35 i.e., develop M2 tumor-associated macrophages, which play a role in the progression and prognosis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] We observed that while N202.1A tumors in the lung induced a low level of CD681 macrophages secreting IL-10, B16 melanoma cells strongly promoted the presence of double-stained CD681IL-101 cells, suggesting the potential of the latter model to induce an immunosuppressive microenvironment. Accordingly, Gil-Bernabè et al 44 have recently observed in lungs from mice injected with B16 melanoma cells the selective recruitment of CD681 macrophages essential for tumor cell survival. These observations are consistent with studies showing that alveolar macrophages in the presence of some growing tumors become immunosuppressive, 33,35 i.e., develop M2 tumor-associated macrophages, which play a role in the progression and prognosis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to this effect includes the role of clotting factors and platelets in such fundamental processes in cancer as cellular growth, angiogenesis, metastasis, inflammation, therapeutic responsiveness and vascular comorbidities, as extensively reviewed in the recent literature [6,7,20,21,25,[84][85][86][87][88][89][90][91]. Notably, pharmacological and genetic strategies targeting TF, FVIIa, thrombin, platelets and other coagulation mechanisms led to anti-tumor and anti-metastatic effects [61,[92][93][94][95][96], which are often comparable to other 'main stream' targeted agents [87,93].…”
Section: Coagulation System As Modulator Of Tumor Initiation Progresmentioning
confidence: 99%
“…Tumor-induced coagulation has a significant role in thrombus formation that is associated with cancer progression [40,41]. However, Tinzaparin treatment of mice at clinically relevant concentration was clearly beneficial over a specific anti-thrombotic treatment, Fondaparinux, strongly suggesting that inhibition of coagulation is not significantly contributing to anti-metastatic activity in a mouse model of experimental metastasis [42].…”
Section: Discussionmentioning
confidence: 99%